Pancasila as the Marriage Legal Idea for Indigenous Women and Ancestors - Tridewiyanti, Kunthi (Law Research Review Quarterly, 2016)
The phenomenon of injustice in the field of marriage for indigenous women and tribesmen continues to occur, including that it can be seen from discriminatory policies. This doctrinal research is expected to answer the problem, because Pancasila should be the legal ideal (recht idÃƒÂ©e) of the foundation of marital law that has "justice" for them. This paper will discuss: First, Pancasila as a legal ideal. Second, Pancasilas is a justified legal ideal using the Pancasila legal theory. Third, Pancasila as the ideal of marriage law. Fourth. Pancasila as a marriage law ideal for indigenous women and followers using the "legal development theory" offered by Mochtar Kusumaatmadjadan Niken Savitri with "feminist legal theory" to address the issue of injustice in the marital field.